The Structural Analysis of the Determinants of Shanghai Real Estate Price - Chen, Zhi (European Scientific Journal, ESJ, 2018)
What are the factors that play the most significant role in affecting Shanghai real estate price? This essay has established an econometric model and uses the perspective of structural analysis to substantiate the real factors that affect the housing price in Shanghai during the 1994— 2015. The essay first collects data from multiple authoritative sources according to potential factors. Then, the essay selects several optimal factors and conducts verification on them. The result is being analyzed. Finally, a conclusion has been reached: factors on the supply side of housing individually have small impact on the price while factors on demand side and policy demonstrate strong impact statistically. This conclusion further suggests that policy implemented by the government with respect to housing price problem in Shanghai could restrain the unreasonable growth to some extent.